2023
DOI: 10.29327/5198985
|View full text |Cite
|
Sign up to set email alerts
|

Direito Civil Famílias

Abstract: Este livro é uma proposta de estudo reflexivo do Direito das Famílias. Como tal, reúne a análise dos institutos inseridos neste ramo, mas não apenas a partir do que deles já foi falado pela doutrina e pela jurisprudência, tradicionais e contemporâneas. Para além da apresentação deste panorama, a incitação ao raciocínio crítico é aspecto particular da obra. Parte-se do pressuposto de que são características essenciais do Direito das Famílias a sua socialidade e a sua vinculação à normativa constitucional. Assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Over the following months, the oil slick spread along the coast, affecting multiple states, including Pernambuco, Alagoas, Sergipe, and Bahia. 69 The Brazilian Navy, following an investigation by the federal police, concluded that a Greek-flagged ship carrying the oil was to blame for the spill. Despite that conclusion, it can be said that the outcome is controversial and requires further reflection.…”
Section: Case Study: Brazilmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the following months, the oil slick spread along the coast, affecting multiple states, including Pernambuco, Alagoas, Sergipe, and Bahia. 69 The Brazilian Navy, following an investigation by the federal police, concluded that a Greek-flagged ship carrying the oil was to blame for the spill. Despite that conclusion, it can be said that the outcome is controversial and requires further reflection.…”
Section: Case Study: Brazilmentioning
confidence: 99%
“…There is nothing in the Convention or in Chapter 8 of Annex I of MARPOL that entitles a coastal State to impose a marine protection levy on a foreign-flagged vessel carrying out an STS operation in its EEZ". 69 Caso M/T "SAN PADRE PIO" (Suíça V. Nigéria), Medidas Provisórias. Caso ITLOS N.º 27. para.…”
Section: Caso M/t "Sanmentioning
confidence: 99%
See 3 more Smart Citations